Reduced competition between tool action neighbors in left hemisphere stroke. (November 2019) - Garcea, Frank E.; Stoll, Harrison; Buxbaum, Laurel J.
Abstract: When pantomiming the use of tools, patients with limb apraxia after left hemisphere stroke (LCVA) produce more spatiotemporal hand action errors with tools associated with conflicting actions for use versus grasp-to-pick-up (e.g., corkscrew) than tools having a single action for both use and grasp (e.g., hammer). There are two possible accounts for this pattern of results. Reduced performance with 'conflict' tools may simply reflect weakened automaticity of use action activation, which is evident only when the use and grasp actions are not redundant. Alternatively, poor use performance may reflect a reduced ability of appropriate tool use actions to compete with task-inappropriate action representations. To address this issue, we developed a Stroop-like experiment in which 21 LCVA and 8 neurotypical participants performed pantomime actions in blocks containing two tools that were similar ("neighbors") in terms of hand action or function, or were unrelated on either dimension. In a congruent condition, they pantomimed the use action associated with the visually presented tool, whereas in an incongruent condition, they pantomimed the use action for the other tool in the block. Relative to controls and other task conditions, LCVA participants showed reductions in hand action errors in incongruent relative to congruent action trials; furthermore, the degree of reduction in this incongruence effect was related to the participants' susceptibility to grasp-on-use conflict in a separate test of pantomime to the sight of tools. Support vector regression lesion-symptom mapping analyses identified the left inferior frontal gyrus, supramarginal gyrus, and superior longitudinal fasciculus as core neuroanatomical sites associated with abnormal performance. Collectively, the results indicate that weakened activation of tool use actions in limb apraxia gives rise to reduced ability of these actions to compete for task-appropriate selection when competition arises within single tools (grasp-on-use conflict) as well as between two tools (reduced neighborhood effects).